State Financial Losses Recovery Through Asset Forfeiture - Raden Yudhi Teguh Santoso; Ainul Azizah; Gautama Budi Arundhati (Rechtenstudent, 2025)
Indonesia, as a state governed by law (rechtstaat), guarantees the protection of its citizens' constitutional rights, including economic rights. However, the existence of corruption classified as an extraordinary crime has undermined the nation’s economic foundations and deprived the people of their economic entitlements. Law enforcement against corruption must not only focus on punishing perpetrators but also prioritize the recovery of state losses through the mechanism of asset forfeiture derived from criminal acts. This study examines the urgency and dynamics of asset forfeiture within the framework of Indonesia's positive law, including the relevance of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, and the Indonesian Penal Code (KUHP) of 2023. Furthermore, it discusses the concept of non-conviction based asset forfeiture and the need for a specific Asset Forfeiture Law as a manifestation of the state's commitment to restoring state finances and upholding the rule of law. This research also analyzes the strategic role of the Prosecutor's Office in the asset recovery process, as well as institutional challenges and inter-agency coordination issues in its implementation.